The wealth of communities war, resources and cooperation in Renaissance Lombardy - Di Tullio, Matteo (Routledge, Taylor & Francis Group, 2016)
"The early sixteenth century was a turbulent time for the Italian peninsula as competing centres of power struggled for political control. Nowhere was this more true than the area contested by Milan and Venice, an area constantly crossed and occupied by rival armies. Investigating the impact of successive crises upon the inhabitants of the Po Valley, this book challenges many fundamental assumptions about the relationship between war and economic development and draws conclusion that have implications for early-modern Europe as a whole"--Provided by publisher